A single-cell atlas of lung homeostasis reveals dynamic changes during development and aging - Hao Jia; Yuan Chang; Yulin Chen; Xiao Chen; Hang Zhang; Xiumeng Hua; Mengda Xu; Yixuan Sheng; Ningning Zhang; Hao Cui; Lei Han; Jian Zhang; et al. (Communications Biology, 2024)
Abstract Aging is a global challenge, marked in the lungs by function decline and structural disorders, which affects the health of the elderly population. To explore anti-aging strategies, we develop a dynamic atlas covering 45 cell types in human lungs, spanning from embryonic development to aging. We aim to apply the discoveries of lung’s development to address aging-related issues. We observe that both epithelial and immune cells undergo a process of acquisition and loss of essential function as they transition from development to aging. During aging, we identify cellular phenotypic alternations that result in reduced pulmonary compliance and compromised immune homeostasis. Furthermore, we find a distinctive expression pattern of the ferritin light chain (FTL) gene, which increases during development but decreases in various types of lung cells during the aging process.